Mesoscopic Neural Representations in Spatial Navigation. Issue 7 (July 2019) - Kunz, Lukas; Maidenbaum, Shachar; Chen, Dong; Wang, Liang; Jacobs, Joshua; Axmacher, Nikolai
Abstract : Recent evidence suggests that mesoscopic neural oscillations measured via intracranial electroencephalography exhibit spatial representations, which were previously only observed at the micro- and macroscopic level of brain organization. Specifically, theta (and gamma) oscillations correlate with movement, speed, distance, specific locations, and goal proximity to boundaries. In entorhinal cortex (EC), they exhibit hexadirectional modulation, which is putatively linked to grid cell activity. Understanding this mesoscopic neural code is crucial because information represented by oscillatory power and phase may complement the information content at other levels of brain organization. Mesoscopic neural oscillations help bridge the gap between single-neuron and macroscopic brain signals of spatial navigation and may provide a mechanistic basis for novel biomarkers and therapeutic targets to treat diseases causing spatial disorientation. Highlights: Neural representations of spatial navigation have mainly been studied at the microscopic level of single neurons or at the macroscopic level of fMRI. Recent intracranial electroencephalography (iEEG) recordings in patients with epilepsy revealed neural representations of spatial features, including travelled distance, goal proximity to boundaries, and grid-like hexadirectional orientation. These representations occur at the mesoscopic level of brain oscillations, particularly in the theta frequency band. Mesoscopic representations of space bridge the gap between their micro- and macroscopic counterparts. Experimentally testable scenarios may explain how the mesoscopic spatial representations relate to single-neuron firing, other neural oscillations, and fMRI signals. Neural spatial representations may offer novel tools for biomarkers of neurological and psychiatric diseases.